The Next Phase in the Digital Revolution: Platforms, Abundant Computing, Growth and Employment - John Zysman; Martin Kenney (The Research Institute of the Finnish Economy (ETLA), 2016)
This report argues that computer-intensive automation (CIAutomation) is likely to change the nature of work and manufacturing value creation in the emerging Platform Economy. The industrial and service changes based on low-cost computation, as they become more generalized, may reverse Robert Gordon's observations about the slowing growth in productivity. However, the increased adoption of CIAutomation also poses profound dilemmas for society that revolve around whether this automation will be used to solely to replace workers or can be integrated into production of goods and services in ways that augment human capacities and intelligence. Finally, we speculate upon the role of the state in in governing and shaping the emergence of the Platform Economy.
Keywords: D78; L86; O33; 330; Platforms; Automation; Gig economy; Governance; Public policy; Automatisierte Produktion; Cloud Computing; Strukturwandel; Sozialer Wandel; Produktivität; Arbeitsmarkt; Good Governance